FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEREMPUAN BERSTATUS MENIKAH UNTUK BEKERJA (STUDI KASUS KOTA SEMARANG) - Fitria Majid; Herniwati Retno Handayani (Universitas Diponegoro, 2012)
ABSTRACT Women want to actualize themselves in development by doing their transition role as labors who participate actively in making living. However, the domestic roles of married women such as taking care of children and housework, causes the decision of married women whether working or no becomes more complex. In addition, the number of women Labor Force Participation Rate in Semarang is still not optimal, which is only about 52%-56%. It means, there is 44% - 48% that hasn’t been optimalized in labor market. Semarang city, the capital of Central Java Province, has geo-strategic location and the highest number of Regional Minimum Wage among 35 other regencies/cities in Central Java, so it attracts people to work in Semarang. The dependent variable of this research was married women decision to work. The independent variables were education leve, husband income level, and family size. In determining research location, this research uses “multistage sampling” method, and the collected data will be analyzed with “Binary Logistic Regression” model. The result of this research shows that the three independent variables used (education, husband income level, and family size) influence positively and significantly on married women decisions to work.